Critical global development studies and work placement: A pedagogical citizenship approach - Franklin Obeng-Odoom (Research in Globalization)
Critical Global development studies (CGDS), built on theoretical foundations in pedagogical citizenship, is widely dismissed for faring poorly in terms of educating students for employment in the ‘real world’. It is usually alleged that there is a misallignment between the skill set of CGDS students and the competencies required for work. But there is dearth of empirical evidence with which to verify the attacks on CGDS. Specifically, how do CGDS students experience work and what are employers’ experiences of working with critical development studies students? Drawing on a thematic analysis of more than 100 reflections by CGDS interns and their employers, this paper shows that most of these interns find internships rewarding, and employers consider CGDS to be competent. CGDs interns are typically described as ‘capable’, ‘quick to learn’, ‘innovative’, ‘independent-minded’ and yet excellent at ‘teamwork’. Employers also commonly describe those CGDS interns who work in research institutions and think tanks as ‘analytical’. This empirical evidence refutes the attacks on CDGS. As CGDS students work in all sectors of society – from private and public to the third sector across the world, these results suggest that CGDS students contribute constructively to reconstructing societies. Overall, the evidence shows that there is room for more, not less, critical global development studies.